IEEE sensors 2016 data - Barrington, James (Cranfield University, 2016)
Raw data for LPGs with periods 167 - 177 um. A single period is represented by each folder containing text files for: - baseline (pre-UV irradiation) - 1 - 6 cycles - normalised spectrum of cycle 6 (baseline - cycle 6) The text files are arranged into 2 tab separated columns for wavelength and intensity. Link to corresponding poster can be found in references.
Keywords: Long period gratings'; '2nd order coupling'; 'Optical Physics not elsewhere classified'